Correlation of Vitamin D and nutritional status in pediatric systemic lupus erythematosus - Muhammad Zulfikar Mahfudz; Harjoedi Adji Tjahjono; Irfan Agus Salim; Fadilah Mutaqin (Pediatric Sciences Journal, 2023)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune illness affecting various organ systems, including the skin, joints, kidneys, cardiovascular, and neurological systems. Because of its immunomodulatory properties, vitamin D has been linked to the etiology and therapy of SLE. The link between vitamin D and nutritional status in pediatric systemic lupus erythematosus (pSLE) is complicated and multifaceted. This study aims to see if there is a link between vitamin D and nutritional status in children with systemic lupus erythematosus. Method: This study design was cross-sectional to determine factors influencing children with SLE. The study was conducted at Saiful Anwar Hospital in Malang from January 1, 2021, to June 30, 2022, and was approved by the hospital's research ethics committee. Statistical analysis was performed using the Shapiro-Wilk test for normality and Pearson correlation with SPSS 25 statistical analysis software. Results: All samples (32 children) were female, with a mean age of 14.1 ± 1.5 years. The mean vitamin D level was 18.32 ± 2.15 ng/mL, mean body mass index (BMI) was 19.51 ± 1.49 kg/m2. Regarding the nutritional status of children with SLE, 10 children were classified as malnourished (30%), while 19 children had good/normal nutritional status (60%). Three children had overweight (10%). There was a positive correlation between BMI and vitamin D in children with SLE (p=0.000, r=0.630). Conclusion: The majority of SLE youngsters have inadequate vitamin D levels. Vitamin D and the nutritional health of children with pediatric systemic lupus erythematosus have a significant favorable association.